Gelled non-toxic bicontinuous microemulsions as promising transdermal drug carriers. (18th August 2021) - Peng, Ke; Sottmann, Thomas; Stubenrauch, Cosima
Abstract : Gelled non-toxic bicontinuous microemulsions have great potentials in transdermal drug delivery. The bicontinuous microemulsion provides optimum drug solubilisation and promotes skin permeation, while the gel network provides mechanical stability and an easy application. For the first time, we have formulated such a gelled non-toxic bicontinuous microemulsion consisting of H2 O, isopropyl myristate (IPM), the non-ionic sugar-based surfactant Plantacare 1200 UP (C12 G1.4 ), 1, 2-octanediol, and the low molecular weight gelator 1, 3:2, 4-dibenzylidene-D-sorbitol (DBS). In this study, we solubilised both hydrophobic and hydrophilic model drugs in the non-toxic bicontinuous microemulsion, namely lidocaine and diclofenac sodium salt. We found that the microemulsion allows for the solubilisation of designated amounts of both model drugs in the same formulation. Interestingly, the combination of both drugs led to the unexpected stabilisation of a scattering one-phase formulation without adding the surfactant Plantacare 1200 UP. Furthermore, the drug-loaded microemulsions were gelled by DBS without altering the phase behaviour. Finally, we found the rheological behaviour of the drug-free and drug-loaded microemulsions to be quite similar. These results suggest that the drug-containing gelled bicontinuous microemulsion is an orthogonal self-assembled system with a high potential for the use in transdermal drug delivery. GRAPHICAL ABSTRACT: UF0001